2008
DOI: 10.1080/13664530701827731
|View full text |Cite
|
Sign up to set email alerts
|

Using e‐learning to support primary trainee teachers’ development of mathematical subject knowledge: An analysis of learning and the impact on confidence

Abstract: In this article we explore the effectiveness of a mathematics subject knowledge development model that integrates conventional distance learning with an e-learning coaching and peer group conferencing environment. The effectiveness of the model in supporting 194 primary (pupils aged 5-11 years) trainee teachers' achievement of the subject knowledge standards (DfEE 1998a) required for qualified teacher status is evaluated and the impact of the model on trainee confidence is explored. Features of the model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…As can be seen, the findings of this study are consistent with previous literature and research on this topic, which showed how primary teachers experience anxiety and negative attitudes towards mathematics (Burgess and Mayes 2008, Ernest 1989, Henderson and Rodrigues 2008, Hodgen and Askew 2007, Murphy 2006, Smith 1996.…”
Section: Discussionsupporting
confidence: 82%
“…As can be seen, the findings of this study are consistent with previous literature and research on this topic, which showed how primary teachers experience anxiety and negative attitudes towards mathematics (Burgess and Mayes 2008, Ernest 1989, Henderson and Rodrigues 2008, Hodgen and Askew 2007, Murphy 2006, Smith 1996.…”
Section: Discussionsupporting
confidence: 82%
“…Additional strategies for the establishment of a social presence were highlighted in the literature examined. Group members with similar interests or roles (Li 2011;Rideout et al 2008;Yeh 2010) provided further opportunities to enhance belongingness; collaboration in small groups (Dickey 2004;Ducan and Barnett 2009;Li 2011) helped to develop trust and more cohesive communities; regular discussions and high levels of support and cooperation among group members (Burgess and Mayes 2008;Vinagre 2017;Yeh 2010) were more likely to drive constructive environments and better performance, and; authentic and practical activities (Satar and Akcan 2018; Swaggerty and Broemmel 2017; Yeh 2010) as well as relevant commenting (Tang and Lam 2014;Vinagre 2017) fostered participation and commitment to the task. The establishment of a social presence was also found when social interaction (process) was prioritised over the completion of the task (product) (Vinagre 2017).…”
Section: The Presences In the Online Teaching And Learning Practicesmentioning
confidence: 99%
“…Key issues in the design of effective online learning environments included an accurate pedagogical approach, relevant and authentic assignments, and appropriate tools and technology. Several aspects related to the former led to teaching and learning impact: providing flexibility to foster self-pace learning while at the time setting clear expectations and timelines for the students (Ducan and Barnett 2009;Jin 2005); targeting individual needs, strengths and interests (Burgess and Mayes 2008;Chambers, Threlfall, and Roper 2012;Coole and Watts 2009;Tai et al 2019), including also preferred e-learning styles (Coole and Watts 2009;Ducan and Barnett 2009), and users' technology experience (Chieu, Herbst, and Weiss 2011); focusing on formative assessment to enhance students' learning (Delfino and Persico 2007;Uribe and Vaughan 2017), with a special attention to peer-to-peer forms of assessment to promote learners' participation and meaningful engagement (Gikandi and Morrow 2016;Wen and Tsai 2008); splitting the whole cohort into smaller groups (e.g., through breakout or chat rooms) for undertaking specific tasks (Biasutti and EL-Deghaidy 2014;Delfino and Persico 2007;Ducan and Barnett 2009;Nicholas and Ng 2009), and; providing an integrated approach in relation to the different knowledge domains (Anderson, Barham, and Northcote 2013;Evens et al 2017;Niess and Gillow-Wiles 2014) as well as the elements involved in the online teaching and learning Table 3. Factors influencing the establishment of a cognitive presence (according to the papers reviewed).…”
Section: The Teaching Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the diverse range of subject knowledge at entry to the one year PGCE programme and the wide geographical spread of the trainees the model of e-learning combined with face-to-face and text based materials demonstrated that all applicants could achieve equally good subject knowledge outcomes that met the national assessment subject knowledge standards in mathematics. (Burgess & Shelton Mayes 2008) Video-conferencing has also been used extensively on ODL programmes, when the trainees are geographically isolated. In Scotland, the training of Gaelic-medium teachers for Gaelic communities is addressed through an ODL ITE programmes involving the use of video-conferencing (see Box 5) this poses some important pedagogic problems.…”
Section: Box 4 Primary Mathematics Subject Knowledge Ukmentioning
confidence: 99%